Avaliação da toxicidade de nanopartículas de óxido de cobre e de óxido de cromo para Daphnia similis e Brachionus calyciflorus - Tavares, Karla Palmieri (2014)
The use of metal nanoparticles has grown exponentially, but there are also concerns about the environmental risk to aquatic biota. Copper oxide nanoparticles (CuO NPs) are frequently employed in antifouling paints, and nanoparticles of chromium oxide (Cr2O3 NPs) have been used as a green pigment. Their extensive use can contaminate aquatic ecosystems, and the toxicological effects of these NPs to the biota are poorly known. In this study, we evaluated the acute toxicity induced by CuO NPs and Cr2O3 NPs, comparing with CuSO4 as Cu2+ ion source and Cr(NO3)3 as Cr3+ ion source , using Daphnia similis and Brachionus calyciflorus. For D. similis, the mean EC50 for CuO NPs was 0.064 mg/L and for CuSO4 was 0.015 mg/L, lower values of EC50 than those available in the literature for D. magna. For B. calyciflorus, the EC50 for CuO NPs was 0.0145 mg/L and for CuSO4 was 0.0029 mg/L. The decrease in toxicity of NPs compared to salt may be due to the fact that CuO NPs tend to agglomerate, which may have reduced the release of Cu2+ in the test medium. The mean EC50 for Cr2O3 NPs was 6.74 mg/L and for Cr(NO3) was 11.98 mg/L for D. similis, whereas for B. calyciflorus was 89.97 mg/L (Cr2O3 NPs) and 14.72 mg/L (Cr(NO3)3). The reduced size of the Cr2O3 NPs (15-30 nm) and the higher Zeta Potential may have contributed to the higher stability in suspension and less potential for agglomeration, partially explaining the higher toxicity of NPs in relation to Cr(NO3)3 salt, which was not observed for B. calyciflorus. CuO NPs were considered very toxic and Cr2O3 NPs were considered dangerous for organisms tested. However, B. calyciflorus was more sensitive to NP of CuO and CuSO4 than D. similis, which showed greater sensitivity to NP Cr2O3 and Cr (NO3)3 in comparison to the rotifer.